Understanding stakeholder networks for nutrition policy: Lessons from a network analysis study in India - Cyriac, Shruthi; Kohli, Neha; Aberman, Noora-Lisa; Pradhan, Mamata; Avula, Rasmi; Menon, Purnima (Wiley, 2017)
India has a decentralized governance setting but there is limited data on how decentralization impacts nutrition policy. Policy actors and their networks are central to the process of decision-making for policy but little is known about the spread and connectedness of diverse actors in the nutrition landscape in India and its multiple states. This research aimed to identify the complex set of inter-connected stakeholders and understand how their interactions influence maternal and child health policy and program decisions related to nutrition. It also aimed to test the use of a participatory network mapping tool to identify policy actors and the scale and scope of actor networks in a nutrition policy space.